By-catch composition of the Patagonian scallop fishery: the fishes - Schejter, Laura (2012)
An inventory of 24 fish species incidentally caught by the Patagonian scallop fleet in the SW Atlantic Ocean is provided for the first time. The most frequent species were Psammobatis spp. (81.36%), Bathyraja brachyurops (75.14%), B. macloviana (73.45%), Patagonotothen ramsayi (66.10%), Merluccius hubbsi (53.67%) and B. albomaculata (50.28 %). Many of the recorded chondrichthyes are considered vulnerable or endangered species. The number of taxa (fishes + invertebrates) that conforms the by-catch of the fishery was increased and updated to nearly 200.